Comparação entre eletrocoagulação e coagulação química como alternativas para o tratamento de água de lavagem de filtros visando seu reciclo em estações de tratamento de água - Martini, Jéssica (2024)
Filter backwash is a critical phase in water treatment plants (WTP) that generates a significant amount of waste. Filter backwash water (FBW) is produced during the cleaning process of filters when the filter media becomes saturated. Reintroducing FBW into WTP can be a valuable and viable alternative for managing this waste, thereby reducing the water demand in WTPs. However, it is imperative to ensure that the reintroduction of FBW does not alter or compromise the water treatment process, and that it maintains the quality and safety of the water distributed to the population. In this context, the objective of this dissertation is to evaluate electrocoagulation (EC) with alum electrodes and chemical coagulation (CC) using alum sulfate (Al2(SO4)3) in the treatment of FBW. The aim is to identify the optimal operational conditions for both processes, with the ultimate goal of facilitating the reuse of FBW in WTP. Samples were collected in WTP of Santa Maria – RS, and tests were conducted using a jar test equipment equipped with 2 L rectangular jars. For the EC process, two groups of alum electrodes were employed, each consisting of 8 electrode plates (8cm x 3cm x 0.05 cm). A continuous current power supply was employed, and the experimental design incorporated both a fractional factorial design and a rotational central composite design to determine the most effective treatment conditions. Both treatments successfully achieved color and turbidity characteristics that allow for the reuse of FBW in WTP, particularly when the optimal operational conditions were applied. In the case of CC, high coagulant doses and elevated initial pH levels were necessary. Using Al2(SO4)3 doses of 230 mg.L-1 and an initial pH of 9.5, it was possible to remove 95% of color and 98% of turbidity, as predicted by the regression model. The primary treatment mechanism observed in CC was sweeping coagulation. In the case of EC, the main reaction mechanism observed was adsorption. Optimal color and turbidity removal occurred with an electric current ranging between 1 and 1.8 A and an initial pH of 6 to 6.5. According to the regression model in EC, it is feasible to achieve 96.9% and 98.9% removal of color and turbidity, respectively, when operated at an initial pH of 6.3 and an electric current of 1.25 A, equivalent to a dose of 95.56 mg.L-1 of Al2(SO4)3. In absolute terms, FBW treated with EC exhibited superior color and turbidity quality compared to FBW treated with CC. Additionally, the pH in EC remained more stable compared to CC. In CC, the removal of TOC and TC was enhanced by the application of high coagulant doses. However, the elevated coagulant doses, combined with an acidic pH at the end of the reaction, led to a substantial concentration of residual alum. In contrast, the sludge produced in the EC exhibited complete flotation, offering the advantage of easy drainage, dehydration, and subsequent disposal of this waste. Despite the slightly higher operational cost associated with EC, it emerges as a better alternative for FBW treatment and reuse in WTP. This preference is attributed to lower concentrations of residual alum and DTS in treated FBW, as well as the favorable characteristics of the sludge formed during the EC process.